Experience with the UK New Enterprise Allowance scheme. (August 2015) - Cameron, Alastair
The New Enterprise Allowance scheme provides support for unemployed people wishing to start a business or become self-employed. Financial support is provided through a weekly allowance and access to loan capital, with business advice provided through volunteer mentors. This paper outlines the introduction of New Enterprise Allowance in the UK, provides an overview of the service and describes the experience of one contractor delivering New Enterprise Allowance in North Scotland.